Analisis Persepsi Wisatawan Terhadap Kualitas Pelayanan Di Pantai Karang Sewu, Kawasan Taman Nasional Bali Barat, Kabupaten Jembrana, Bali - Ida Ayu Ketut Utari; I Nyoman Sukma Arida (JURNAL DESTINASI PARIWISATA, 2021)
Based on the number of tourist visits to Karang Sewu Beach that is fluctuating or up and down therefore researchers want to analyze the perception of tourists to the quality of service in Karang Sewu Beach because tourist satisfaction is a benchmark in the success of tourist attraction. The method used in this study is quantitatively descriptive. by using the technique of analysis namely importance performance analysis. data collection techniques used are observations, interviews, questionnaires and documentation. and scale measurement techniques using the likert scale. sampling techniques used are sampling quotas as well as to measure the size of samples using the 1993, Maholtra formula with the number of samples obtained is as many as 85 respondents. Based importance performance analysis method is a higher level of importance than the performance level with the average interest level is 4.55 and the performance level is 2.84. Therefore, there needs to be an improvement in performance such as: cleanliness of environmental conditions at Karang Sewu Beach, good service during first impression to tourists, explanation of all the information needed by tourists is very clear and detailed, the availability of facilities in Karang Sewu Beach such as seating, stalls, supporting facilities such as toilets, trash cans, parking lots, employees very appreciative and putting tourists first in Karang Sewu Beach. Advice or recommendation in this study is for the management of Karang Sewu Beach to improve performance based on the quality of service with attributes that are considered lacking in the eyes of tourists and maintain indicators that are superior in the eyes of tourists. Keyword : Tourism, Service Quality, Importance Performance Analysis